Non-linear Text in Theses - Mohd. Noor, Faridah Noor (Journal of Modern Languages, 2017)
This study attempts to study the types and amount of nonlinear text present in Masters’ theses. The paper shows that non-linear texts are vital in conveying information and findings in academic writing. Teachers of academic writing may find some of the insights of this study relevant for classroom instruction. Students could be taught how to use non-linear texts in order to present findings clearly and accurately.